If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1m + 2 = 0 Reorder the terms: 2 + -1m = 0 Solving 2 + -1m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1m = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1m = 0 + -2 -1m = 0 + -2 Combine like terms: 0 + -2 = -2 -1m = -2 Divide each side by '-1'. m = 2 Simplifying m = 2
| 3u^9*2x^4u^4*5x= | | -29/41-(-12/41) | | 6x^2-13=281 | | 1-3v=-20 | | 15n^2+17n+6=0 | | 6x-13=281 | | 1+4b=5 | | 1x/4-1=1x/7+2 | | 5+4m=29 | | 2-2p=6 | | 1.7=fraction | | -9=-14+b | | 0.285x^2-2x+2=0 | | 16=18+z | | x/2+17=22 | | 2p+5=25 | | -17=-15+x | | f(x)=895+30g | | 15n^2+17n=4 | | -2=-20+y | | -5b+4=39 | | 12+m=-8 | | B/3+6=24 | | -3n+4=19 | | 19=-8+n | | 6+5f+11r-7+3f+5(x+3)= | | -6(3x+9)+7= | | 25p+6p^2=-4 | | x^4+4x^3+(-8x^2)+2=0 | | x^2-4x+13=29 | | -3-5x=-18 | | x^4+4x^3(-8x^2)+2=0 |